Pannexins Are Potential New Players in the Regulation of Cerebral Homeostasis during Sleep-Wake Cycle - Shestopalov, Valery I.; Panchin, Yuri; Tarasova, Olga S.; Gaynullina, Dina; Kovalzon, Vladimir M. (Frontiers in Cellular Neuroscience, 2017)
During brain homeostasis, both neurons and astroglia release ATP that is rapidly converted to adenosine in the extracellular space. Pannexin1 (Panx1) hemichannels represent a major conduit of non-vesicular ATP release from brain cells. Previous studies have shown that Panx1-/- mice possess severe disruption of the sleep-wake cycle. Here, we review experimental data supporting the involvement of pannexins in the coordination of fundamental sleep-associated brain processes, such as neuronal activity and regulation of cerebrovascular tone. Panx1 hemichannels are likely implicated in the regulation of the sleep-wake cycle via an indirect effect of released ATP on adenosine receptors and through interaction with other somnogens, such as IL-1β, TNFα and prostaglandin D2. In addition to the recently established role of Panx1 in the regulation of endothelium-dependent arterial dilation, similar signaling pathways are the major cellular component of neurovascular coupling. The new discovered role of pannexins in sleep regulation may have broad implications in coordinating neuronal activity and homeostatic housekeeping processes during the sleep-wake cycle.